Besmirching "Bezhin Meadow": Ivan Bunin's "Night Conversation." - Thomas Gaiton Marullo (Studies in 20th & 21st Century Literature, 1985)
Bunin's "Night Conversation" (1912) counters two conceptions of Russian cultural life that he considered erroneous: the intelligentsia's idealization of the narod or "folk" and their reputed adherence to the realist tradition of Russian literature. Bunin does this by fashioning "Night Conversation" as a polemic with Turgenev's "Bezhin Meadow" and by carrying his argument into three facets of his work: portrait, conversation, and setting. "Night Conversation" can thus be seen as marking a crucial transition in the portrayal of the folk in Russian literature as well as in Bunin's own evolution as a writer. It signals a revamping of the peasant-hero from "realist" to "contemporary" and, what is more important, the implicit willingness of Russia's "last barin in literature" to assist in the passage.
Keywords: Night Conversation; Bezhin Meadow; Ivan Bunin; Russian culture; narod; folk; Turgenev; portrait; conversation; setting; Russian folk literature; realist; contemporary